Fast and slow carbonaceous BOD speciation of sewage effluent - Abdullah, Norizan; Abdul Rahman, Norazah; Zainudin, Zaki (Institution of Engineers Malaysia, 2010)
The Biochemical Oxygen Demand (BOD) test has been a long standing test method to quantify the amount of biodegradable organic matter present in a water sample. The test is typically conducted over a 5-day period (BOD5), with the sample being incubated at 20°C. It has been a long standing assumption that over the 5-day period, most of the organic should be stabilized and typically under normal conditions this may be true. Recent developments however have shown that there may significant variation for certain types of wastewater samples where the organic fraction may consists of more slowly biodegradable organics (such as particulate organic carbon) than readily biodegradable organics (dissolved organics). Under such circumstances, the results of the BOD5 test may lead to serious underestimation of the total amount of organics present hence also the pollution strength. This study aims to speciate the two organic fractions under two distinct categories termed slow-BOD and fast-BOD. The speciation is done by filtering the samples(0.12 um) to separate the dissolved and particulates fractions. The results showed there was a distinct variation between the filtered and unfiltered samples, where the amount of organics stabilized within the five day period for the unfiltered sample was approximately 50% of the total BOD measured. After this period the oxygen depletion continued, which in turn was attributed to the slowly biodegradable organics.